Penanaman nilai dalam materi ajar pembelajaran daring perguruan tinggi - Adriyanto, Andreas Rio; Santosa, Imam; Syarief, Achmad (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
Online learning offers cross-space and time, so students get flexibility in their time and place. Participants in online learning are larger than in traditional face-to-face classes. The utilization of internet networks has an impact on changes in learning culture. The position of students is required to be more individuals in managing learning. The role of the tutor revealed by Ki Hajar Dewantara has shifted its function. Educators cannot be directly involved in online learning. In online learning, educators function more than mediators and facilitators. Transfer of noble values, intellectualism, ethics, responsibility, honesty, and things that are reflective is not as easy as face-to-face learning. However, the application of technology in education is a necessity because the current generation is a digital generation whose daily life is inseparable from digital interactions. This study aims to see how the application of reflective aspects in learning material with a focus on the dominant material in the affective domain. Experiments will be conducted on learning video material on two groups of students. One group of students becomes a control group, while the other becomes an experimental group. In the control group, neutral learning videos will be used, while the experimental group will use features that apply the principle of coherence, personalization, and story method. The effectiveness of learning will be measured by evaluating the form of retention test, aptitude test, comprehensive transfer test, and problem-solving transfer test. This publication is ongoing research. It is expected that further discussions related to the methodology and features being tested can be raised. The application of technology that functions as an instrument of innovation in the cultivation of noble values of Indonesian culture is expected to be a reference in the design of teaching materials for online learning, especially for material from the affective domain.DOI: 10.17977/um022v5i12020p039